2020
DOI: 10.1093/ije/dyaa065
|View full text |Cite
|
Sign up to set email alerts
|

Inference about causation from examination of familial confounding (ICE FALCON): a model for assessing causation analogous to Mendelian randomization

Abstract: Background We developed a method to make Inference about Causation from Examination of FAmiliaL CONfounding (ICE FALCON) using observational data for related individuals and considering changes in a pair of regression coefficients. ICE FALCON has some similarities to Mendelian randomization (MR) but uses in effect all the familial determinants of the exposure, not just those captured by measured genetic variants, and does not require genetic data nor make strong assumptions. ICE FALCON can as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…We also tested for any association between the BMI and DNAm. Since at least two studies have indicated that the BMI causes DNAm rather than vice versa, we employed a linear regression model with BMI as independent variable, adjusted for age 31,32 . No signi cant association was detected (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…We also tested for any association between the BMI and DNAm. Since at least two studies have indicated that the BMI causes DNAm rather than vice versa, we employed a linear regression model with BMI as independent variable, adjusted for age 31,32 . No signi cant association was detected (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…The interrelationship between BMI and DNA methylation is complex and possibly bidirectional. Li et al carried out the ICE FALCON (Inference about Causation from Examination of Familial Confounding) 34 analysis in 479 Australian women from twin families and found that BMI had a causal effect on DNA methylation level at ABCG1 cg06500161 35 . Wahl et al calculated a weighted genetic risk score (GRS) based on 29 known BMI SNPs and observed the significant direct effects of BMI‐weighted GRS on methylations of ABCG1 cg06500161 ( p = 6.4E‐05) and SREBF1 cg11024682 ( p = 4.1E‐03) 13 .…”
Section: Discussionmentioning
confidence: 99%
“…We explored the causal inference between SES and obesity using Inference about Causation through Examination of FAmiliaL CONfounding (ICE FALCON), a statistical modeling approach used to obtain observational data for related individuals, particularly twin pairs (24‐27). ICE FALCON makes causal inference using the familial similarity of an exposure, which has similarities with bidirectional Mendelian randomization (28). By causal, it is meant that, were it possible to vary a predictor measure experimentally, the expected value of the outcome measure would change (25).…”
Section: Methodsmentioning
confidence: 99%